Colon Cleansing before Colonoscopy: Does Oral Sodium Phosphate Solution Still Make Sense? - Douglas K Rex; Stephen J Vanner (Canadian Journal of Gastroenterology)
Oral sodium phosphate (NaP) solution has been withdrawn from the market in the United States but remains available for over-the-counter purchase for bowel preparation for colonoscopy in Canada. The present review summarizes recent data regarding the renal toxicity of oral NaP as well as its efficacy and tolerability relative to other preparations. Given the availability of effective alternatives to NaP solution, its use for colonoscopy preparation in Canada should be limited. Candidate patients for oral NaP solution should be assessed for eligibility and preparation instructions should adhere to the current recommendations for maximizing the safety of oral NaP.